A NEW AMPHICYONID (MAMMALIA, CARNIVORA, AMPHICYONIDAE) FROM THE LATE MIDDLE MIOCENE OF NORTHERN THAILAND AND A REVIEW OF THE AMPHICYONINE RECORD IN ASIA - Peigné S.; Chaimanee Y.; Yamee C.; Tian P.; Jaeger J.-J. (My University, 2006)
Recent field research conducted in the middle Miocene basin of Mae Moh, northern Thailand, allow discovering dental remains of a new amphicyonid (Mammalia, Carnivora, Amphicyonidae). A thorough comparison with all known Asian and non-Asian Miocene genera of Amphicyonidae supports the assignment of these specimens to a new amphicyonine, Maemohcyon potisati gen. et sp. nov. We propose the first review of the fossil record of the Amphicyoninae and we discuss the possible geographic origin and phylogenetic relationships of this new taxon. It appears that Maemohcyon does not have close relationships with contemporary (Amphicyon, Pseudocyon, Ischyrocyon, Pliocyon) or earlier (Ictiocyon, Pseudarctos, Cynelos, Ysengrinia) genera. We suggest that the Maemohcyon lineage probably arrived much earlier than 13 Ma (age of Mae Moh fauna) and evolved in this insulated region until the late middle Miocene. © 2004 Elsevier Ltd. All rights reserved.
Keywords: AMPHICYONIDAE; AMPHICYONINAE; MIOCENE; NEW GENUS; THAILAND; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен